RADIKULOPATI LUMBAL - Muhammad Hafiz Moulvi; Jan Izaac Ferdinandus (Neurologi Manado, 2023)
Low back pain is one of the neuromusculoskeletal complaint that is commonly found in practice. Low back pain usually happens in men above 40 yo, and women around 50-60 yo. The cause of low back pain varies, such as nerve root compression, trauma, bone degeneration, disc herniation, infection, inflammation, vascular disturbance, or can be neoplasm. Management of low back pain can be carried-out non-operatively or operatively, depending on the severity, the syumptoms that arise, and the response to non-operative treatment.